Prolonged measurement improves the assessment of the barrier function of the esophago‐gastric junction by high‐resolution manometry. Issue 2 (14th August 2016) - Jasper, D.; Freitas‐Queiroz, N.; Hollenstein, M.; Misselwitz, B.; Layer, P.; Navarro‐Rodriguez, T.; Fox, M.; Keller, J.
Abstract: Background: Etiology of gastro‐esophageal reflux disease (GERD) is multifactorial, but incompetence of the esophago‐gastric junction (EGJ) appears to be of crucial importance. Established manometric parameters for assessment of EGJ barrier function are sub‐optimal, potentially because they reflect only a very brief (up to 30 seconds), not necessarily representative period. This prospective, case–control study tested the performance of novel, high‐resolution manometry (HRM) parameters of EGJ function in the assessment of GERD. Methods: Patients with reflux symptoms and healthy controls (HC) underwent standard HRM and 24‐hour pH±impedance measurements. EGJ morphology, lower esophageal sphincter pressure integral (LES‐PI), EGJ contractile integral (EGJ‐CI) were compared with total‐EGJ‐CI, a novel parameter summarizing EGJ barrier function during the entire HRM protocol. Esophageal acid exposure ≥4.2%/24 h ( A‐Reflux‐pos ) or ≥73 reflux episodes in 24 hours ( V‐Reflux‐pos ) were considered pathological. Key Results: Sixty five HC and 452 patients completed HRM, 380 (84%) patients underwent ambulatory reflux‐monitoring. LES‐PI, EGJ‐CI and total‐EGJ‐CI correlated with EGJ morphology subtypes (all P <.00001). Only total‐EGJ‐CI was consistently lower in A‐Reflux‐pos and V‐Reflux‐pos subjects compared with HC and patients without GERD. Total‐EGJ‐CI was also the single best parameter for prediction of pathological reflux (optimal cut‐off 47 mmHg cm, AUC 0.746, P <.0001). This cut‐off value, approximately 1 SD below the mean normal value, showed modest sensitivity 54% and positive predictive value 46%, but good specificity 85% and negative predictive value 89% for GERD diagnosis. Conclusion & Inferences: Total EGJ‐CI, a new metric that summarizes EGJ contractility over time, allows an improved assessment of EGJ barrier function. Pathological reflux is unlikely if this metric is within the upper two‐thirds of the normal range. Abstract : Total‐esophagogastric junction contractile integral (EGJ‐CI), a new metric summarizing EGJ contractility over the entire length of standard HRM, was tested in 65 healthy controls and 452 GERD patients and proved to be superior over conventional metrics and other HRM metrics for prediction of pathological reflux. In particular, the negative predictive value approached 90% if total‐EGJ‐CI was within the upper two‐thirds of the normal range. These findings suggest that GERD is highly unlikely if the EGJ can maintain normal contractility over several minutes.